Pembingkaian Perjuangan Tanah Orang Mentawai Dalam Konflik Kehutanan - Nurhayati, Nurhayati; Afrizal, Afrizal; Jendrius, Jendrius (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
The geographical location and growth patterns have never been touched by human intervention, making the Mentawai forest have a unique composition. Implementation of economic growth in land control through market mechanisms and state intervention. State intervention in the land and forestry sectors changes the land use map on Siberut Island. Limiting residents' rights in managing, utilizing natural resources, and ownership. This study focuses on the Siberut forestry conflict in Saliguma Village, Siberut Tengah District, Mentawai Islands Regency. The Provincial Government reserves ± 20,030 hectares of land for PT-Biomass Andalan Energi for Calliandra (Calliandra Calotthyrsus), gamal (Gliricidia Sepium), and lamtoro (Leucaena leucocephala) Industrial Plants. The purpose of the study was to describe the framing and basis for framing of the Saliguma Village people in the conflict with PT. BAE. Using the Symbolic Interactionism theory developed by Herbert Blummer with a qualitative research approach. Researchers collected and analyzed data in the form of words, human actions, interviewed Traditional Leaders, Village Heads, Sikebukkat Uma, land cultivators, and sympathizers of the Saliguma Village people. The results of the study rejected the investment plan to develop Industrial Plantation Forests in Saliguma Village. The Saliguma Village people framed the land as ancestral land, sacred land, land as a source of livelihood, customary land, their village is prone to flooding, and they were deceived by the company. The basis for the framing of the Saliguma Village people is the ancestral rights to the land and the sustainability of the lives of the Saliguma Village people.Letak geografis serta pola pertumbuhannya belum pernah tersentuh campur tangan manusia membuat hutan Mentawai memiliki komposisi yang khas. Implementasi pertumbuhan ekonomi penguasaan tanah melalui mekanisme pasar dan intervensi Negara. Intervensi negara bidang pertanahan dan kehutanan merubah peta penggunaan lahan di pulau Siberut. Membatasi hak warga dalam pengelolaan, memanfaatkan sumber daya alam, dan pemilikan. Penelitian ini fokus pada konflik kehutanan Siberut di Desa Saliguma Kecamatan Siberut Tengah, Kabupaten Kepulauan Mentawai. Pemerintah Provinsi mencadangkan tanah seluas ±20.030 hektar untuk PT-Biomass Andalan Energi guna Tanaman Industri kaliandra (Calliandra Calotthyrsus), gamal (Gliricidia Sepium), dan lamtoro (Leucaena leucocephala). Tujuan penelitian adalah untuk mendeskripsikan framing dan dasar framing orang Desa Saliguma dalam konflik dengan PT. BAE. Menggunakan teori Interaksionisme Simbolik dikembangkan Herbert Blummer dengan pendekatan penelitian kualitatif. Peneliti mengumpulkan dan menganalisis data berupa kata-kata, perbuatan manusia, mewawancarai Pimpinan Adat, Kepala Desa, Sikebukkat Uma, penggarap tanah, dan simpatisan orang Desa Saliguma. Hasil penelitian menolak rencana investasi mengembangkan Hutan Tananaman Indutsri di Desa Saliguma. Orang Desa Saliguma memframing tanah tersebut tanah leluhur, tanah sakral, tanah sumber mata pencarian, tanah adat, Desa mereka rawan banjir, dan mereka ditipu oleh perusahaan. Dasar framing orang Desa Saliguma adalah hak leluhur atas tanah dan keberlajutan kehidupan orang-orang Desa Saliguma.